2020
DOI: 10.18060/23258
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Service-Learning Outcomes Measurement Scale (S-LOMS)

Abstract: Service-learning as a transformative pedagogy has been adopted within Hong Kong's tertiary education sector for over a decade; however, the lack of a standardized and validated measurement instrument to assess its student learning outcomes has been an obstacle to its further development. The current research study, collaboratively conducted by Lingnan University, The Hong Kong Polytechnic University, Hong Kong Baptist University, and The Education University of Hong Kong, therefore aims to develop such a measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 44 publications
(51 reference statements)
4
26
0
Order By: Relevance
“…The current study continues the measurement instrument validation journey. This paper reports the validation results of testing S-LOMS with a new sample through confirmatory factor analysis (CFA) against the above factor structure that emerged in the previous EFA study (Snell & Lau, 2020). It is intended that subsequent research not reported here will test for other types of validity regarding S-LOMS, such as test-retest reliability, and will then use S-LOMS to measure developmental outcomes for students through before and after administration around servicelearning experience.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The current study continues the measurement instrument validation journey. This paper reports the validation results of testing S-LOMS with a new sample through confirmatory factor analysis (CFA) against the above factor structure that emerged in the previous EFA study (Snell & Lau, 2020). It is intended that subsequent research not reported here will test for other types of validity regarding S-LOMS, such as test-retest reliability, and will then use S-LOMS to measure developmental outcomes for students through before and after administration around servicelearning experience.…”
Section: Introductionmentioning
confidence: 95%
“…Astin & Sax, 1998;Astin, Vogelgesang, In comparison with similar measurement instruments that have been adopted in the past, S-LOMS carries several merits. First, it has been designed for the context of Hong Kong, reflecting the local culture and recent developments within the higher education sector there (Snell & Lau, 2020). Second, the set of domains included in S-LOMS comprehensively covers the desired developmental outcomes of Hong Kong based service-learning programs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Snell and Lau (2020), in the process of being adapted to the unique institutional and cultural context of tertiary education in Hong Kong, servicelearning has acquired four local emphases that are distinct from typical western applications. First, there is greater emphasis on personal and moral development than on the furtherance of democratic ideals.…”
Section: Service-learning and Its Development In Hong Kongmentioning
confidence: 99%